2010
DOI: 10.1111/j.1464-410x.2010.09815.x
|View full text |Cite
|
Sign up to set email alerts
|

Defecation disturbances after cystectomy for urinary bladder cancer

Abstract: • Outcome variables were dichotomized and the results are presented as relative risks with 95% confidence interval. RESULTS• The questionnaire was returned from 452 (92%) of 491 identified patients. Up to 30% reported problems with the physiological emptying process of stool (bowel movement, sensory rectal function, awareness of need for defecation, motoric rectal and anal function, straining ability).• A sense of decreased straining capacity was reported by 20% of the men and women with non-continent urostomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
3
4
0
1
Order By: Relevance
“…Our results are supported by a Swedish population-based study that reported postsurgery defecation problems occurring in up to 30% of patients, indicating bowel problems may have a significant impact on HRQoL 38. Moreover, the value of the exercise-based rehabilitation intervention was a 10% significant decrease in symptoms of dyspnea in the intervention group compared with the standard group.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are supported by a Swedish population-based study that reported postsurgery defecation problems occurring in up to 30% of patients, indicating bowel problems may have a significant impact on HRQoL 38. Moreover, the value of the exercise-based rehabilitation intervention was a 10% significant decrease in symptoms of dyspnea in the intervention group compared with the standard group.…”
Section: Discussionsupporting
confidence: 83%
“…The percentage of items rated “important” or “very important” varied across the domains: medical (95%, 95% CI 94–97%), physical (86%, 95% CI 84–88%), practical (77%, 95% CI 75–80%), emotional (67%, 95% CI 63–70%), social (61%, 95% CI 58–64%), and spiritual (40%, 95% CI 35–44%). The ten most highly ranked informational needs were from the medical [5], physical [3], and practical [2] domains (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in cancer treatment have increased survival rates1 and the population of cancer survivors is continuously growing. Being cured of cancer does not necessarily mean being in good health, since we know from our research that the long-term consequences of treatment can have a devastating impact on the quality of life of cancer survivors 5 12 13 27. For this reason it is essential to evaluate the post-treatment physical symptoms experienced by survivors as well as their long-term quality of life.…”
Section: Discussionmentioning
confidence: 99%